A Comparative Analysis of Intelligence Studies Programmes in the United Kingdom and Nigerian Universities - Isa, Awwal; Nte , Ngboawaji Daniel; Featherstone, Clairmont Roger; Baba-Ahmadu, Abdulaziz (Police Studies Review, 2021)
As the world collectively recognized the onerous task of collective security and the liberalization of intelligence studies, different nations have encouraged the introduction and management of intelligence studies programmes in their university system. Consequently, this work is a comparative analysis of intelligence studies as an academic discipline in the United Kingdom and Nigeria. Relying extensively on historiographical and content analysis of data and facts logically arranged in tandem with the social sciences traditional research enterprise, the study found out, unlike the UK, with a substantially longer history of intelligence studies, Nigeria is still crawling with the idea with just two private universities-Novena University and Afe Babalola University. Furthermore, the study found out that while Nigeria has a lot to learn from the UK style of intelligence studies, both countries should better develop unique albeit parallel intelligence analytical frameworks to suit their domestic needs while cooperation will be more useful in areas of manpower training, development, foundational literature, and academic professionalism.